Copying hierarchical leaders’ voices? Acoustic plasticity in female Japanese macaques - Lemasson, Alban (Sci Rep, 2016)
It has been historically claimed that call production in nonhuman primates has been shaped by genetic factors, although, recently socially-guided plasticity and cortical control during vocal exchanges have been observed. In humans, context-dependent vocal convergence with relatives, friends or leaders’ voices can be found. Comparative studies with monkeys and apes presenting tolerant social organizations have demonstrated that affiliative bonding is the determining factor of convergence. We tested whether vocal copying could also exist in a primate species with a despotic social organization. We compared the degree of inter-individual similarity of contact calls in two groups of Japanese macaques as a function of age, dominance rank, maternal kin and affiliative bonds. We found a positive relationship between dyadic acoustic similarity and female rank differences. Since most call exchanges were initiated by dominant females and since this species is known for the ability of responders to acoustically match initiators’ calls, we conclude that high social status may motivate vocal convergence in this despotic society. Accordingly, intra-individual comparisons showed that isolated calls were more stereotyped than exchanged calls, and that dominants had more stereotyped voices than subordinates. This opens new lines of research with regard to social motivation guiding acoustic plasticity in primates.